2008
DOI: 10.1093/ejo/cjn057
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo surface and mechanical properties of coated orthodontic archwires

Abstract: This study examined the mechanical and physical properties of retrieved coated nickel-titanium (NiTi) archwires compared with unused samples. Ultraesthetic 0.016 inch coated archwires (G&H(R) Wire Company) were investigated. Ten as-received wires were subjected to a three-point bending test using conventional and self-ligating bracket systems. Surface roughness of the coating was measured with a contact stylus profilometer. Optical and scanning electron microscopes were used to assess surface topography. Ten a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 12 publications
8
107
3
Order By: Relevance
“…Under the microscope, the coated archwires discolored, delaminated and their surface roughness increased after use. It was concluded that coated archwires have a low esthetic value, with 25% of the coating being lost after 33 days (15). The variation between initial and post-deflection roughness of the Group ANT was not significant, as this group presented high initial roughness values.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Under the microscope, the coated archwires discolored, delaminated and their surface roughness increased after use. It was concluded that coated archwires have a low esthetic value, with 25% of the coating being lost after 33 days (15). The variation between initial and post-deflection roughness of the Group ANT was not significant, as this group presented high initial roughness values.…”
Section: Discussionmentioning
confidence: 90%
“…The quantity of tooth movement during orthodontic treatment depends on the force on the two surfaces, as well as roughness and nature of the materials involved (14). Problems associated with the loss of coating during clinical use have been related in the literature, and for this reason, simulation of clinical use was performed by means of the deflection test, in order to observe these changes (15,16). In this study, 70 orthodontic Niti wires coated with PTFE, epoxy resin, gold/rhodium metals and a group without coating were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Some authors have experienced difficulties with these coated archwires, claiming that the color tends to change with time 6 and that the coating splits during use in the mouth, exposing the underlying metal. [7][8][9] However, despite these problems, these wires continue to be marketed and used in clinical practice, mainly when an esthetic alternative for a rectangular cross-sectional archwire is necessary. The surface quality of archwires affects the area of surface contact and influences the esthetic result, the corrosion behavior, the plaque accumulation, and the biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The surface quality of archwires affects the area of surface contact and influences the esthetic result, the corrosion behavior, the plaque accumulation, and the biocompatibility. 7 Among the properties in the search for the ideal archwire, the surface topography plays an important role and can critically modify the efficiency of orthodontic components. 10,11 Further, increased surface roughness can increase the friction coefficient 12 and is an essential factor in determining the effectiveness of archwire-guided tooth movement.…”
Section: Introductionmentioning
confidence: 99%